Implementasi Sistem Pengelolaan Hotel Berbasis Syariah: Studi pada Hotel Satria Wisata Parepare - Muhammad Ilham; Suci Indah Sari; Reno Indah Prima Nisa; Mila Jenudi (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
This study aims to analyze the implementation of sharia-based hotel management at Hotel Satria Wisata Parepare. Using a qualitative field research approach, data were collected through interviews, observation, and documentation involving hotel management. The findings indicate that the hotel has implemented sharia principles in its management practices, including operational management, services, human resources, and facilities, in accordance with DSN-MUI Fatwa No. 108 of 2016. Key implementations include halal assurance for products, identity verification for guests, sharia-compliant employee conduct, and the provision of adequate worship facilities. However, the implementation remains managerial in nature and has not yet been supported by a formal sharia supervisory structure. This study contributes to the empirical understanding of sharia hotel management practices at the local level.